Propuesta gastronómica para el desarrollo sociocultural en el Cantón Buena Fe, año 2019 - Ruiz Avellan, Yalicsa Andreina (2020)
This research project was developed based on the problems evidenced in the Buena Fe canton, Los Ríos Province, in terms of gastronomy and the social and cultural development of the town, for which the respective objectives framed and supported were established with proper research and data collection for decision-making focused on solving all the problems found. In Chapter 1, the topic of research based on international, national, local and institutional contexts will be developed, raising the respective problematic situation, and in the same way the respective justification for setting the objectives to be achieved. Chapter 2, will contain the necessary theoretical support in the conceptual framework, referential and research background attached to the subject under investigation, supported by reference of the most representative authors, all this research assembly to conclude with the hypotheses of the case. In Chapter 3, the results obtained from data collection, subsequent representation with the respective statistical tables and graphic representation will be announced. The respective proposal will be developed in Chapter 4, outlining the objectives that need to be achieved as part of the structure of the proposed alternative to solve the case, in addition the respective conclusions and recommendations regarding the improvement of gastronomy and sociocultural development of the Buena Fe song.